Detection of antihelmintic resistance to 15% albendazole of gastrointestinal nematodes in hair lambs of a Venezuelan flock - Angulo Cubillán, Francisco; Urdaneta, Angela; Urdaneta, Margelys; Parra, Alexander; Chacín, Everts; Ramírez Barrios, Roger (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
In order to assess the antihelmintic efficacy of Albendazole in a 15% concentration against gastrointestinal nematodes in hair lambs, it was made a research with 30 crossbreed West African lambs, three months old, naturally infected. The lambs were divided in two groups, one treated with the antihelmintic and else as control untreated. The faeces samples were taken directly of the rectum, previous to the treatment and at seven and fourteen days post treatment (DPT), analyzed through McMaster modified technique. To evaluate the antihelmintic efficacy was used the faecal eggs count reduction test (FECRT) “in vivo” and the identification of the infective larvaes recovered from faecal cultures. The treatment did not showed any effect against the FECRT, observed in the treated groups means of 5,110 and 5,790 eggs per gram of faeces (EPG) and the control 3,452 and 3,330 EPG, to the seven and 14 DPT, respectively. From faecal cultures infective larvaes of Haemonchus spp.,Trichostrongylus spp., Bunostomun spp. and Strongyloides papillosus were recovered. Antihelmintic resistance was detected in gastrointestinal nematodes against Albendazole in hair lambs of a Venezuelan flock.